Exercise effect on sex hormone and bone density of menopausal female - Hu, J. M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study is to discuss the effect of exercise on female sex hormone and bone density.